2022
DOI: 10.1186/s40468-022-00210-4
|View full text |Cite
|
Sign up to set email alerts
|

Learning-oriented assessment in the classroom: the contribution of self-assessment and critical thinking to EFL learners’ academic engagement and self-esteem

Abstract: The core of self-assessment (CSA) and critical thinking (CT) empower learners to observe and evaluate themselves. Although the literature on CSA and CT reflects a long history, little is known about their contributions to the learners’ academic engagement (AE) and self-esteem (SE), particularly in the EFL context. Therefore, the present investigation intended to explore a structural model of English as a Foreign Language (EFL) university students’ CSA, CT, and SE. Accordingly, the Core of Self-assessment Quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…Specifically, the finding indicates that students may increase their academic motivation and satisfaction by practicing these approaches. The findings of the previous research, such as [ 5 , 49 , 50 ] provide support for the conclusions that were made in this article. They concluded that using efficient strategies may help EFL students boost their emotional involvement, self-aid concepts, motivation, and social bonds, as well as lessen the amount of burnout that the students suffer.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Specifically, the finding indicates that students may increase their academic motivation and satisfaction by practicing these approaches. The findings of the previous research, such as [ 5 , 49 , 50 ] provide support for the conclusions that were made in this article. They concluded that using efficient strategies may help EFL students boost their emotional involvement, self-aid concepts, motivation, and social bonds, as well as lessen the amount of burnout that the students suffer.…”
Section: Discussionsupporting
confidence: 87%
“…As a result, substantial breakthroughs in the creation of a more efficient teaching approach are proposed. According to the findings of [ 2 , 50 ] employing methods such as continual monitoring, planning, and evaluation may help students overcome problems faced throughout language instruction. Furthermore, empirical research has shown that people who have a strong sense of their own self-worth are more engaged in classroom activities and have lower levels of inhibition when faced with difficult academic assignments.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing the Pearson R statistical method, the findings revealed that there existed no significant relationship between self-esteem and class engagement among the selected students from Cavite City, as indicated by a p-value of 0.124. Conversely, a study in Language Testing in Asia offers pedagogical insights for educators, emphasizing the role of self-assessment and critical thinking in enhancing students' academic engagement and selfesteem (Riswanto et al, 2022) [12] . Furthermore, various research studies employ diverse research focuses and methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…They came to the conclusion that students who are able to think critically are better equipped to develop their own methods of reflective learning. According to the findings of another research by [ 46 ], if EFL instructors acquire sufficient understanding about critical thinking, they will be able to use it in their own classes. Comparable reasons for the failure to properly deploy CT in EFL classrooms were cited by [ 47 ], who pointed to EFL instructors’ limited comprehension of CT and the discrepancy between teachers’ positive sentiments regarding CT and their actual classroom actions.…”
Section: Overviewmentioning
confidence: 99%